Development of fibre-reinforced thermoplastics for tough and damage tolerant composites : processing, characterization and applications - Lee, Pearl Sullivan Pek Wah. (2008)
The main parts of the project were (i) to develop thermoplastic composites using a solvent method and (ii) to develop interleaved composites.